A case study of designing technology-enhanced learning in an elementary school in Singapore. (3rd July 2017) - Tay, Lee Yong; Melwani, Mohamed; Ong, Jemuel Liangyu; Ng, Ken Renjie
ABSTRACT: This case study presents how teachers from an elementary school in Singapore design learning for their students, leveraging on the use of information and communications technology (ICT). The school in this case study is one of the eight future schools in Singapore under the FutureSchools@Singapore programme. The school provides one-to-one computing learning devices and wireless Internet access for its students. Teachers from the school, teaching various grade levels and subject matters, were interviewed on how they use current and prevalent online technologies to enhance and transform teaching practices. In-depth discussion interviews with the teachers about their pedagogical practices were analysed according to the six learning experiences – acquisition, inquiry, practice, production, discussion and collaboration. Structural elements surrounding this case study (e.g. conditions surrounding the school) were also taken into consideration. The rich description and in-depth interviews with the teachers can also provide models for other teachers to emulate and reflect upon. This case study highlights the following: pedagogical differences and similarities in different subject areas, that students' learning experience depends on how lessons are being designed, structural elements that affect ICT use and integration, and the need for students to learn to use before they can use ICT to learn.